Do university residential experiences contribute to holistic education?. Issue 1 (2nd January 2020) - Cheng, Michelle W.T.; Chan, Cecilia K. Y.
ABSTRACT: Can residential experiences help undergraduates develop holistic competencies? To answer this question, a study was conducted based on the insights of 211 residents in Hong Kong. Deductive and inductive content analyses were respectively used to examine residence life outcomes, particularly in holistic competencies, and to categorise the types of residential experiences deemed to be effective for these outcomes. Results revealed that participation in hall activities led to the development of residence life outcomes, including justice, humanity, wisdom, courage, transcendence, and wellbeing. Furthermore, planning/organising hall activities greatly improved students' sense of justice while interpersonal dynamics facilitated the improvement of humanity only. The analyses indicated that students without specific engagement in hall activities were also able to develop temperance, particularly in self-regulation. Recommendations are suggested based on the analyses. It is hoped that this study might help inform policy-making processes to provide better residential environment that is beneficial to student holistic development.